A holistic vision of the academic and sports development of elite Spanish track and field athletes - Asensio Castañeda, E.; Navarro, R. M.; Chamorro, J. L.; Ospina-Betancurt, J. (International Journal of Environmental Research and Public Health, 2024)
Background: Combining sports and studies could be stressful, but beneficial for the athletes` career development. This study explores resources and barriers in the combination of the sports and academic life spheres during the lifespan of elite Spanish track-and-field athletes.